Enhancing Food Security and Nutrition Among Rural Elderly: Addressing Socio Economic Challenges Amid Economic Reforms - Balqis Romoke Kareem; Adekunle Olufemi Oloyede; Azeezat Bukola Omitola; Tobi Isreal Akinremi (CV Media Inti Teknologi, 2025)
Background: This study investigates the relationship between nutritional outcomes and economic vulnerability among elderly populations in rural Nigeria, analysing the effects of market liberalization, agricultural reforms, and policy changes on nutritional status in light of sustainable development goals of Nigeria.Aims and scope: To examine how economic reforms impact the nutritional security of senior citizens (60 years and older) living in rural Ogbomoso North, with focus on the relationship between economic indicators and nutritional outcomes during periods of major economic transition.Methods: A cross-sectional mixed-methods study was conducted with 310 elderly participants (60 years of age and older) during a period of major economic reforms, examining both economic indicators and nutritional status.Results: Prevalence rates showed 32.7% overweight, 18.3% obesity, and 10.5% underweight among participants. Obesity was more prevalent in women (22.1%) compared to men (14.5%). The study revealed that 65% of participants modified their food choices based on market prices rather than nutritional value, particularly during periods of economic instability.Conclusion: The nutritional security of elderly populations in rural Nigeria is significantly impacted by socioeconomic factors and economic reforms. The findings highlight the need for coordinated policy approaches that integrate economic sustainability initiatives with nutritional interventions to protect vulnerable elderly populations during economic transitions.